The mediator role of organizational innovativeness between organizational culture and organizational effectiveness - Ashraf‍, Giti; Abd. Kadir, Suhaida; Lope Pihie, Zaidatol Akmaliah; Mat Rashid, Abdullah (European Centre for Research, Training and Development, 2014)
Organizational culture and organizational innovativeness are viewed as important factors for improving the organizational effectiveness in institutions of higher education. The aim of this study was to examine the correlations among organizational culture, organizational innovativeness and organizational effectiveness. Moreover, the mediating role of organizational innovativeness between organizational culture and organizational effectiveness was studied.The method used in the study was survey research. Based on the cluster sampling method, all full time faculty members from five branches of Islamic Azad University (IAU), Pars Province, Iran, were included in the sample of the study. The number of respondents was 369 participants. For measuring variables, three questionnaires were employed. The findings indicated that the adhocracy culture, market culture and clan culture were found to have significant positive correlations with organizational innovativeness and organizational effectiveness. However, hierarchy culture showed no significant relationship with either organizational innovativeness or organizational effectiveness. Additionally, organizational innovativeness partially mediated the relationships among clan, adhocracy and market cultures with organizational effectiveness.Therefore, organizational culture not only directly influences both innovativeness and effectiveness but also influences effectiveness through innovation. The university administrators should be aware of the benefits from the implementation of a culture that supports innovation in order to assure the effectiveness of universities.